2018
DOI: 10.7249/rr2754
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Los Angeles County's Mental Health Community Engagement Campaign

Abstract: The Los Angeles County Department of Mental Health (LAC DMH) recently undertook a youth-targeted social marketing campaign that sought to increase community engagement around barriers to mental health access. LAC DMH's campaign utilized funds from Proposition 63, which was signed into law as the Mental Health Services Act (MHSA). The MHSA levied a 1 percent state-level tax on all California personal incomes over $1 million, resulting in a substantial investment in mental health. A portion of those funds is spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 7 publications
(7 reference statements)
1
13
0
Order By: Relevance
“…Among those exposed, 8 percent reported visiting the LACDMH website. This is the same percentage observed among survey respondents ages 26 or older in our evaluation of the LACDMH COVID-19 campaign, which was done about one year prior to this report's publication (Collins, Eberhart, Shearer, et al, 2021). The numbers may not be comparable because the current survey also included adults ages 18 to 25 and because characteristics of the pandemic-and perhaps stress levels-have changed over time.…”
Section: Whywerise Summary and Conclusionsupporting
confidence: 52%
See 4 more Smart Citations
“…Among those exposed, 8 percent reported visiting the LACDMH website. This is the same percentage observed among survey respondents ages 26 or older in our evaluation of the LACDMH COVID-19 campaign, which was done about one year prior to this report's publication (Collins, Eberhart, Shearer, et al, 2021). The numbers may not be comparable because the current survey also included adults ages 18 to 25 and because characteristics of the pandemic-and perhaps stress levels-have changed over time.…”
Section: Whywerise Summary and Conclusionsupporting
confidence: 52%
“…We had made these same points in our evaluation of the LACDMH COVID-19 campaign (Collins, Eberhart, Shearer, et al, 2021) and suggested that Los Angeles County feature the LACDMH website address and Help Line number more prominently in its outdoor and print images instead of in broadcast media, where such details are harder to process and memorize. County staff did so in the materials evaluated in this report, but it does not appear to have increased uptake.…”
Section: Whywerise Summary and Conclusionmentioning
confidence: 73%
See 3 more Smart Citations